FUTURISTIC ISLAMIC STUDIES IN AGUS MUSTOFA'S AUDIOVISUAL EXEGESIS - Widi Lestari, Wahyuni; Supriadi, Akhmad; Munirah (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2023)
Agus Mustofa is a controversial figure because his thoughts are considered deviant. Even so, he remains productive in writing and interpreting verses from the Al-Qur'an on his YouTube channel, which has hundreds of thousands of subscribers. Agus Mustofa's academic background is nuclear engineering, not Qur'Änic exegesis. This study examines the sources, methods, validity, and implications of Agus Mustofa's interpretations. It employs interpretive epistemological theory and mass communication theory to accomplish these objectives. Data is collected from a Agus Mustofa's YouTube channel, Sufistic Islamic Studies. The results show that first, the sources used by Agus Mustofa are tafsir bil ma'tsur and tafsir bil ra'yi. Second, the method used is mauá¸Å«Ê¿Ä« with a scientific approach. Third, the validity of the data obtained through coherence is inconsistent using interpretive sources, whereas correspondence and pragmatism are new in the world of interpretation. Fourth, Agus Mustofa's interpretation provides positive cognitive, affective, and behavioral impacts on society.